Prove that:

Question:

Prove that:

$\cos ^{2}\left(\frac{\pi}{4}-x\right)-\sin ^{2}\left(\frac{\pi}{4}-x\right)=\sin 2 x$

Solution:

LHS $=\cos ^{2}\left(\frac{\pi}{4}-x\right)-\sin ^{2}\left(\frac{\pi}{4}-x\right)$

$=\cos 2\left(\frac{\pi}{4}-x\right)$       $\left[\because \cos ^{2} \alpha-\sin ^{2} \alpha=\cos 2 \alpha\right]$

$=\cos \left(\frac{\pi}{2}-2 x\right)$

$=\sin 2 x=\mathrm{RHS}$           $\left[\because \cos \left(\frac{\pi}{2}-2 \alpha\right)=\sin 2 \alpha\right]$

Hence proved.

Leave a comment

None
Free Study Material